2022
DOI: 10.1097/as9.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Type With Colorectal Surgery Outcomes and Costs at a Safety-Net Hospital

Abstract: Objective: Association of insurance type with colorectal surgical complications, textbook outcomes (TO), and cost in a safety-net hospital (SNH). Background: SNHs have higher surgical complications and costs compared to low-burden hospitals. How does presentation acuity and insurance type influence colorectal surgical outcomes? Methods: Retrospective cohort study using single-site National Surgical Quality Improvement Program (2013–2019) with cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Of note, insurance status was also strongly associated with the likelihood to undergo emergent resection of CC. Tetley et al similarly noted an association of insurance type with colorectal surgery outcomes 30 . Other studies have also demonstrated the impact of social vulnerability and residential segregation on the likelihood to undergo emergent versus elective colon surgery 31 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note, insurance status was also strongly associated with the likelihood to undergo emergent resection of CC. Tetley et al similarly noted an association of insurance type with colorectal surgery outcomes 30 . Other studies have also demonstrated the impact of social vulnerability and residential segregation on the likelihood to undergo emergent versus elective colon surgery 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Tetley et al similarly noted an association of insurance type with colorectal surgery outcomes. 30 Other studies have also demonstrated the impact of social vulnerability and residential segregation on the likelihood to undergo emergent versus elective colon surgery. 31 In the AI model, four of the five most important variables associated with emergent surgery were clinicopathologic and operative factors, demonstrating the importance of adhering to oncologic standards of care.…”
Section: Discussionmentioning
confidence: 99%
“…Uninsured and Medicaid patients are more likely to present acutely and undergo emergent colectomy for CRC as compared with privately insured individuals. 3 31 Even when patients are seen in a timely fashion to pursue elective management, uninsured or publicly insured patients are more likely to decline surgery, which may impact their overall survival. 32 33 When these patients do undergo surgery, they are less likely to receive laparoscopic or robotic surgery compared with privately insured patients.…”
Section: Barriers To Colorectal Surgery Care Among Uninsured and Unde...mentioning
confidence: 99%
“…1 2 This is particularly true for patients with benign and malignant colorectal surgery conditions that often require longitudinal care and costly surgical treatment. 3 The objectives of this chapter are twofold. First, we seek to explore clinical outcomes for colorectal surgery patients who are uninsured or underinsured and outline barriers to accessing optimal care.…”
mentioning
confidence: 99%
“…Urgent surgeries have worse surgical outcomes than elective procedures . In addition, urgent cases are more prevalent than emergent cases in vulnerable populations . Furthermore, the large numbers of patients in these databases enable detecting significant differences that may not be usable at a health care–system level.…”
Section: Introductionmentioning
confidence: 99%